Nicotine replacement therapy as a smoking cessation tool for adolescents: an update - Beis, Ioannis; Dimou, Anastasios; Kotoulas, Serafeim-Chrysovalantis; Pataka, Athanasia (Frontiers in Psychiatry, 2025)
BackgroundAdolescent smoking is a significant public health concern, as early nicotine addiction leads to more severe addiction and reduced cessation success during adulthood. While nicotine replacement therapy (NRT) is an effective smoking cessation tool in adults, its efficacy in adolescents is less clear.ObjectiveThis systematic review evaluates the effectiveness and safety of NRT for smoking cessation in adolescents.MethodsA comprehensive search of PubMed and Cochrane Library databases identified 12 studies (randomized controlled trials and observational) examining NRT in adolescents. Outcomes included smoking cessation rates, withdrawal symptom relief, smoking reduction, and adverse events.ResultsNRT demonstrated limited success in long-term smoking cessation among adolescents, with low cessation rates that often declined post-treatment. However, NRT was effective in reducing smoking frequency and in managing withdrawal symptoms in some cases. The safety profile was generally favourable, with mild side effects such as skin irritation, headaches, and nausea.ConclusionWhile NRT can reduce smoking and alleviate withdrawal symptoms, its effectiveness in sustaining long-term cessation in adolescents is limited. Adherence challenges and side effects suggest a need for complementary behavioural support and further research into tailored NRT strategies for this population.